Chemical Antibody Mimics Inhibit Cadherin‐Mediated Cell–Cell Adhesion: A Promising Strategy for Cancer Therapy. (27th November 2019) - Medina Rangel, Paulina X.; Moroni, Elena; Merlier, Franck; Gheber, Levi A.; Vago, Razi; Tse Sum Bui, Bernadette; Haupt, Karsten
Abstract: One of the most promising strategies to treat cancer is the use of therapeutic antibodies that disrupt cell–cell adhesion mediated by dysregulated cadherins. The principal site where cell–cell adhesion occurs encompasses Trp2 found at the N‐terminal region of the protein. Herein, we employed the naturally exposed highly conserved peptide Asp1‐Trp2‐Val3‐Ile4‐Pro5‐Pro6‐Ile7, as epitope to prepare molecularly imprinted polymer nanoparticles (MIP‐NPs) to recognize cadherins. Since MIP‐NPs target the site responsible for adhesion, they were more potent than commercially available therapeutic antibodies for inhibiting cell–cell adhesion in cell aggregation assays, and for completely disrupting three‐dimensional tumor spheroids as well as inhibiting invasion of HeLa cells. These biocompatible supramolecular anti‐adhesives may potentially be used as immunotherapeutic or sensitizing agents to enhance antitumor effects of chemotherapy. Abstract : Molekular geprägte Polymer‐Nanopartikel (MIP‐NPs) blockieren die N‐terminale Region von Cadherinen, das für Zell‐Zell‐Adhäsion verantwortliche Zentrum. Die MIP‐NPs imitieren in Krebsbehandlungen eingesetzte therapeutische Antikörper durch Störung der Zell‐Zell‐Adhäsion, wie durch die Auflösung dreidimensionaler Tumor‐Sphäroide menschlicher Gebärmutterhals‐Adenokarzinom‐Zellen (HeLa) bestätigt wird.